Männer Liebe : ein Handbuch für Schwule und alle, die es werden wollen - Frings, Matthias; Kraushaar, Elmar (Hamburg: Rowolt Taschenbuch Verlag, 1982)
"Matthias Frings ; Elmar Kraushaar Fonds Suzan Daniel (FSD)"